Genetic diversity and flowering in Clianthus and New Zealand Sophora (Fabaceae) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Molecular Biology at Massey University, Palmerston North, New Zealand - Song, Jiancheng (Massey University, 2005)
Clianthus and New Zealand Sophora species are woody legumes endemic to New Zealand, with high ornamental value and biodiversity significance. Research was conducted to address the fact that little is known about the details of their developmental characteristics, genetic structure and relatedness of the wild populations, and their molecular mechanism of flowering. Genetic diversity and relatedness of all remaining wild populations of Clianthus and samples of all New Zealand Sophora species were investigated using ISSR and AFLP markers. Genetic relationships were established for Sophora species, Clianthus wild populations and cultivars, and most individuals in each of the wild Clianthus populations. The molecular evidence did not support the recent separation on morphological grounds of the two Clianthus species, C. maximus and C. puniceus. Postharvest treatments were tested to extend vase life of the short-lived cut Clianthus maximus and Sophora tetraptera flowers. Appropriately treated Clianthus cut flowers lasted 10-12 days in the vase, with over 80% of flowers opening. Similar postharvest treatments did not improve the vase performance of cut Sophora flowers. Detailed calendars of vegetative and reproductive growth, and of floral ontogeny were developed for Clianthus and Sophora. Contrasting behaviours of both vegetative and reproductive growth were observed between these two legumes. A long period of summer-autumn dormancy of vegetative and reproductive growth in Sophora, and mass abortion of initiated Clianthus inflorescences during most of the year were observed. Unusual floral ontogeny processes, with precocious carpel initiation and delayed petal development, were observed in both species. An efficient two-step quantitative real-time RT-PCR protocol for detailed gene expression analysis of large numbers of samples was developed using SYBR Green DNA dye and a LightCycler instrument. The consistency of this protocol was optimised with regards to sample and template preparation, primer design, and determination of appropriate internal controls for gene expression quantification. Differences of gene expression in the range of 5-7 orders were effectively detected. Putative partial homologues of LEAFY, APETALAI, PISTILLATA, and AGAMOUS were isolated from both Clianthus and Sophora. Detailed temporal and spatial expression of each floral identity gene was investigated using quantitative real-time RT-PCR. The expression patterns, together with the sequence similarity, showed that these new isolated gene fragments were most probably LEAFY, APETALAI, PISTILLATA, and AGAMOUS homologues in Clianthus and Sophora, and that the ABC model of floral development is generally applicable to both species. However, there were important variations in temporal expression patterns compared to those of herbaceous species. A bimodal expression pattern of LEAFY and APETALAI homologues was observed in Sophora, but not in Clianthus, coincident with their contrasting patterns of floral initiation and development.
Keywords: Kakabeak; Kowhai; Fields of Research::270000 Biological Sciences::270200 Genetics::270201 Gene expression